Captivity, Citizenship, and the Ethics of Otherwise in the Society-of-Captives Thesis: A Commentary on Arrigo. (June 2013) - Brown, Michelle
In this engagement with Professor Bruce Arrigo's psychological jurisprudence model, I explore his critique of captivity and risk management. I am particularly interested in his claims that incarceration culminates in society's own captivity, that the most destructive aspect of captivity is its foreclosing of human difference and potentiality, and that a praxis that is both clinical and mindful might point a way out. By way of a case anecdote, I interrogate several of the key terms in Arrigo's formulation— citizenship, reform, revolution, and praxis —in an effort to further conjugate from the ground up such an innovative and important set of possibilities.